2014
DOI: 10.1371/journal.pone.0100260
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Exotoxin Production by Mobile Genetic Element SCCmec-Encoded psm-mec RNA Is Conserved in Staphylococcal Species

Abstract: Staphylococcal species acquire antibiotic resistance by incorporating the mobile-genetic element SCCmec. We previously found that SCCmec-encoded psm-mec RNA suppresses exotoxin production as a regulatory RNA, and the psm-mec translation product increases biofilm formation in Staphylococcus aureus. Here, we examined whether the regulatory role of psm-mec on host bacterial virulence properties is conserved among other staphylococcal species, S. epidermidis and S. haemolyticus, both of which are important causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…While we observed gene regulatory changes that were due to the psm-mec srRNA, they mostly comprised metabolic (e.g., riboflavin and purin/pyrimidine synthesis) rather than virulence genes, and were inconsistent between the two strains. Notably, the results of the previously claimed impact of the psm-mec locus on virulence would be negative [ 13 , 15 , 18 ], contrasting the positive effect we observed in the mouse sepsis model. Such a gene regulatory mechanism can thus be ruled out as underlying psm-mec -mediated development of S .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…While we observed gene regulatory changes that were due to the psm-mec srRNA, they mostly comprised metabolic (e.g., riboflavin and purin/pyrimidine synthesis) rather than virulence genes, and were inconsistent between the two strains. Notably, the results of the previously claimed impact of the psm-mec locus on virulence would be negative [ 13 , 15 , 18 ], contrasting the positive effect we observed in the mouse sepsis model. Such a gene regulatory mechanism can thus be ruled out as underlying psm-mec -mediated development of S .…”
Section: Resultscontrasting
confidence: 99%
“…As a previous study suggested that the psm-mec srRNA leads to gene regulatory changes in S . epidermidis [ 15 ], based on the introduction of a psm-mec expressing plasmid into S . epidermidis , we also directly investigated whether the psm-mec locus has a gene regulatory impact in S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Berlon et al showed that decreased PSM-mec production is associated with significantly increased PSMα, β, delta-toxin in MRSA SSTI isolates compared with HAP and IE (6). Moreover, PSM-mec vector-transformed S. epidermidis and S. haemolyticus had a 30% reduction in their combined PSMα and delta-toxin output compared with their null-vector transformed counterparts, suggesting that the PSM-mec downregulation of PSM production is conserved in the Staphylococcus family (30). Given that MSSA lacks the SCCmec cassette and by extension PSM-mec, total MSSA PSM production may be higher than total MRSA PSM production, even though the relative proportions of PSMs produced may have similar profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination success of the ST764 clone might be related to the psm‐mec mutation, but this requires further investigation. The psm‐mec is present not only in MRSA, but also in methicillin‐resistant coagulase‐negative Staphylococci, including Staphylococcus epidermidis and Staphylococcus haemolyticus . Additional studies are needed to investigate the relation of psm‐mec mutations to the bacterial phenotype or specific clinical features of MRSA diseases as well as methicillin‐resistant coagulase‐negative Staphylococci diseases.…”
Section: The Psm‐mec Mutations and Their Correspondence To Sccmec Typmentioning
confidence: 99%